Aggression Against Police Officers and Behavior Toward Citizens: Reciprocal Influence or Common Causes? - van Reemst, Lisa; Fischer, Tamar; Weerman, Frank (Frontiers in Psychology, 2022)
Police officers are often the victim of aggression by citizens, which has negative consequences for them and society in general. Therefore, it is important to gain knowledge about related factors. This study examines to what extent experiencing aggression as a police officer is related to their patience with citizens and use of force weapons and tools. Two hypotheses based on the victim-offender overlap are examined: that aggression experiences and dealing with citizens influence each other or that they have common causes. This study was conducted on the basis of a longitudinal questionnaire survey among police officers (N=693). The results show that behavior towards citizens, including patience with citizens and the use of force is related to the aggression police officers experience. The association diminishes when common causes, in this case socio-demographic and work-related characteristics are taken into account, but does not disappear. No direct support is found for reciprocal influence. Implications and suggestions for further research are described.